KONSTRUKSI MAKNA DAN SIMBOL ROMANTIK DALAM PUISI-PUISI ARCO TRANSEPT DENGAN PENDEKATAN SEMIOTIKA PIERCE - Christina Natalia Setyawati; Munaris Munaris; Heru Prasetyo (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2023)
As one of the literary works that use connotative, symbolic language, full of aesthetic metaphors, poetry has implicit value in the lines of words or analogies that are strung together to display messages in different ways. Transept's poems are full of signs and implicit messages, making the author interested in studying some of Transept's poems with Pierce's semiotic approach to construct the meaning of poetry. This research is expected to contribute to developing an understanding of poetry from a semiotic perspective, providing greater insight into language and culture. Through descriptive qualitative method, the author describes icons, symbols, and indexes in some of Transept's poems. The research results obtained are the discovery of 8 symbols, 7 icons, and 2 indexes in the poem “Jiwa” which emphasizes the sense of loss like a sea storm that swayed the boat; 8 symbols, 8 icons, and 7 indexes in the poem “Di Tubuh Bumi Kita Tumbuh dengan Tabah Ibu” which makes the mother and the universe as an analogy of love; 8 symbols, 5 icons, and 4 indexes in the poem “Sepetak Rumah” which make the island of Sumatera a representation of a big dream an a patch of house a small dream; 9 symbols, 8 icons, and 7 indexes in the poem “Biarkan Kenangan Menjelma Daun” which makes trees a representation of love and falling leaves a memory